Anchoring of Consumers Inflation Expectations: Evidence from Microdata - Lena Dräger; Michael J. Lamla (Hamburg University, Department Socioeconomics, 2013)
In this paper we explore the degree of anchoring of consumers long-run inflation expectations. If expectations are firmly anchored, short- and long-run expectations should show no comovement in response to transitory shocks. Utilizing the University of Michigan Survey of Consumers rotating panel microstructure, we can identify changes in inflation expectations of individual consumers. Our results indicate that long-run inflation expectations became more anchored over time. While the degree of comovement fell significantly after 1996, the probability of a joint adjustment stayed constant. Regarding the possible determinants, we find that consumers rising interest rate expectations and perceived news on the monetary policy stance have a detrimental effect on the anchoring of long-run expectations. This effect is no longer present in the post-1996 period. Notably, a positive effect of perceived news on government debt on the degree of comovement emerges after 1996, alluding to a potentially problematic link between fiscal and monetary policy.
Keywords: E31; E52; D84; 330; Anchoring; inflation expectations; microdata